(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Terminology translation is a specialty within the broader field of translation that focuses on the accurate and precise transfer of terminology from one language to another. In this article, we discuss the different types of correspondence in terminological translation, what they mean, and the strategies used to achieve them